An approach to equivalent damping ratio of vertically mixed structures based on response error minimization. Issue 72 (May 2015) - Huang, Wei; Qian, Jiang; Zhou, Zhi; Fu, Qiushi
Abstract: Damping property of vertically mixed structure is hard to identify, especially in the design stage since it is strongly rely on the configuration of the two component structural parts. In this paper, a decoupling approximation for dynamic response analysis of the vertically mixed structure is proposed. The optimal equivalent uniform damping ratio can be evaluated in a sense of response error minimization. It is calculated by using the superposition response spectrum method which takes the full frequency content of the ground motion into consideration rather than the harmonic excitation at a specified frequency only. The equivalent uniform damping ratios presented here are then validated by comparison with full time history analysis. Over the most part of the ( R ω – R m ) parametrical plane, the response error is relatively small for the each component structural parts. And then, the proposed damping ratios are tested in actual MDOF concrete/steel irregular structures. It is shown that the proposed procedure is proved to be feasible in use for practical design. Highlights: The equivalent uniform damping ratio of vertically mixed structure is investigated. A procedure was proposed for calculating a optional equivalent damping ration based on response error minimization. Response spectrum of the ground motion has been taken into consideration instead of harmonic excitation. Responses computed by using the equivalent uniform damping ratio compare well with that by exact time history analysis.